Does gender affect the professional Competence of Babol dental students? A self-assessment study (Babol University of Medical Sciences, 2023)
Background and purpose: Examining students' opinions in order to acquire clinical skills can be considered as one of the activities that facilitate learning in the clinical environment. Therefore, the opinion of students about their professional competence is very important apart from the students. So we were able to study due to the lack of information in this area. Professional qualification and factors related to it in dental students of Babol University of Medical Sciences by self-assessment method. Materials and Methods: A self-assessment questionnaire designed based on the chapters of dentistry courses that its reliability was determined and completed by students. After collecting data SPSS22 software was used for data analysis. Chi-square statistical tests, Fisher's exact test and one-way ANOVA test were used, and a significance level of less than 0.05 was considered significant. Results: This study was conducted on 50 students including 21 men (42%) and 29 women (58%). Students scored the most in the prosthetics section and the lowest in the health section. In general, students' skills were reported to be higher in the restorative department and the lowest in the oral and dental surgery department. No significant relationship was found between the professional competence of dental students and gender Conclusion: In this study, the level of students' skills in most sections was good from their point of view. It is necessary for dental schools to make constructive changes in learning according to the students' point of view, so that with more encouragement and desire, it will lead to sustainable learning.